Progression of externalizing disorders into anxiety disorders: Longitudinal transitions in the first three decades of life. (March 2022) - Knappe, Susanne; Martini, Julia; Muris, Peter; Wittchen, Hans-Ulrich; Beesdo-Baum, Katja
Abstract: Background: There is a notable comorbidity between externalizing disorders and anxiety disorders, which may be explained by the co-occurrence of two prevalent early-onset disorders, by shared vulnerability and risk factors, or as evidence that one disorder group might be causally related to the other. Aim: To investigate the longitudinal trajectories of externalizing disorders, their interplay with anxiety disorders, and putative predictors for symptom progression in youth. Methods: 1053 adolescents (14–17 years) from the general population were assessed at baseline and prospectively at 2, 4, and 10-year follow-up using a standardized interview of mental disorders (DIA-X/M-CIDI) to assess "early" (oppositional-defiant disorder, conduct disorder, ADHD) and "late" (antisocial behavior, substance use disorders) externalizing disorders as well as anxiety disorders. Longitudinal associations and predictors for symptom progression were examined using Kaplan-Meier-analyses. Results: Lifetime prevalence of early externalizing disorders were 9.1% and 6.4% among those with and without any anxiety disorder. A late externalizing disorder was reported by 50.3% of those with an early externalizing disorder and in 26.6% of those with any anxiety disorder. Both early (HR: 1.5, 95%CI: 1.0–2.3) and late externalizing disorders (HR: 2.1, 95%CI: 1.7–2.6) were associated with incident anxiety disorders. Higher parental rejection, lower volitional inhibition, and higher volitional avoidance predicted incident anxiety disorders among those with early externalizing disorders. Discussion: Early externalizing disorders likely follow a homotypic continuity (to late externalizing disorders) and/or a heterotypic continuity to anxiety disorders, and thus appear as a useful target for prevention and early intervention. Highlights: There is a notable comorbidity between externalizing disorders and anxiety disorders. Among anxiety disordered-youth, 9.1% also reported core symptoms of ODD, CD or ADHD. Similarly, anxiety and substance use or antisocial behavior were highly comorbid. Progression from early externalizing to incident anxiety was predicted by parental rejection and volitional inhibition. Early externalizing disorders thus appear as a useful target for preventive interventions in anxiety disorders.